Título Padrão - Silva, Eliana Neves Pereira da; Andrade, Roberia de Lourdes de Vasconcelos (Informação em Pauta, 2020)
This reseach was done in colaboration with the coordinators of the Pastoral Communications from the Archdiocese of Maceio and aims to identify the perception which those coordineators have about the printed newspaper O Semeador as an oficial source of propagation of religion information from the Archdiocese in times of digital evangelisation. The methodology that was used was bibliographic and descriptive with a qualitative approach. The sample consisted of 42 parishes from the Archdiocese of Maceio and the instrument of data collection used was a questionnaire for the coordinators of the Pastoral Communications.The results of his research revealed that the coordinators of the Pastoral Communications of Maceió evaluated positively the newspaper O Semeador and the digital medias as tools of propagation of religion information for evangelisation, being Facebook the most used social media. To conclude, the main challenge of O Semeador newspaper is to be more recognised by those who work with communication at the parishes.